Hydrodynamics and mass transport in wall tube and microjet electrodes: Effect of vortex formation and cell geometry on limiting currents - Melville, J; Simjee, N; Unwin, P; Coles, B; Compton, R (2002)
Using FIDAP, a finite element method simulation package, investigations into the effect of inlet wall thickness on the flow pattern occurring in the wall tube electrode or microjet electrode have been carried out. Simulation results show that vortex formation, observed above minimum solution velocity thresholds and missing from analytical treatments describing the flow, can have a critical effect on the hydrodynamics and hence on measured limiting currents. In addition, the current response for different-sized ring electrodes has been simulated at a range of speeds and suggests that the thickness of the jet tube wall and vortex formation can have an effect at both of these electrodes and radially offset microdisks. The latter are often used experimentally via the empirical maximization of observed currents. The dangers of applying approximate theory to these surprisingly complex devices are stressed.